Analysis of a Permo-Triassic polarity transition in different absolute reconstructions of Pangaea, considering a model with features of the present Earth magnetic field - Vizán, H.; Van Zele, M. A. (2007)
The main objective of this paper is to show that the distribution of transitional palaeomagnetic data recorded at 250 Ma are in agreement with simulated data that depend on the sampling site, using a model that considers features of the Present Earth magnetic field. The analysis was performed comparing simulated reversals with the Permo-Triassic polarity transition recorded in the Siberian Trap Basalts. The palaeomagnetic data were corrected according to the Palaeo-latitude and Palaeo-longitude of Siberia (absolute reconstruction) at 250 Ma using hotspot tracks. To obtain the motion of Siberia relative to hotspots from the Present time back to 250 Ma, three different Pangaea models were considered (Pangaea A, Pangaea A2, Pangaea B). In spite of the uncertainties associated with the use of hotspot frameworks and Pangaea configurations, both the modelled and recorded data show a remarkable fit when absolute reconstructions of Pangaea A and A2 configurations are performed. The agreement between both simulated and recorded data suggests that similar features to that of the Present Earth magnetic field could have been involved in reversals since the Permo-Triassic. JCR Journal open